Comparative study: Distance education institutes as learning organizations in North Cyprus and UK - Aksal, Fahriye A.; Birol, Cem; Silman, Fatos (Ani Yayincilik, 2008)
Problem Statement: Continuous change and improvements for the quality of organizational development, communication flow and knowledge sharing are crucial within institutions. Recent studies have paid a great deal of attention to the importance of learning organisations and emphasize distance education practices as an innovative strategy. This study fills a gap in the literature by using a comparative study to examine the distance education institutes as learning organisations. The study is significant as it compares the performance of distance education institutes as learning organizations. It also helps to identify quality improvements of learning organisations and provides insights to evaluate the integration of sharing learning in higher education practices within different cultural contexts. Purpose of the Study: The purpose of the study is to investigate the comparison between the performances of the distance education institutes in North Cyprus and the UK Higher Education Institutions. These institutes' performances as learning organizations give a competitive advantage to their higher education system. Methods: The qualitative research method, including in-depth interviews, researcher observations and self-reports, were used to examine these institutes. Data were then analyzed thematically and triangulated. The participants from North Cyprus and UK were purposefully selected as a sample on a voluntary basis. The multiple data collection techniques were reviewed by experts from Turkey, UK and United States and piloted in order to increase the credibility of the research. Findings and Results: Findings revealed that higher education institutions need to use distance education practices as an innovative strategy for continuous improvement. In addition, findings show that the distance education institute in the UK performs better as a learning organization than the distance education institute in North Cyprus, which has limited infrastructure and lacks a collective vision. Conclusions and Recommendations: The research findings suggest that developing a learning organization with distance education practices provides an opportunity for the higher education system to extend its influence on external and multicultural environments. There is also an increasing need to provide strategic planning and evaluation of its effectiveness for the development of distance education institutes as learning organizations. In addition to the two cases examined, other comparisons could also be made considering the cultural dimensions. Furthermore, social interaction such as dialogue and inquiry can be explored using in-depth investigation to enrich other dimensions of learning organizations and improve organizational performance.
Keywords: comparative study; distance education; higher education; learning organization